Seasonal variations in levels of Heavy metals in muscles of crab Sesarma boulengeri collected from Al-Garaf canal at Thi Qar province, Iraq - A. Hussein, Sadek; K. Fahad, Kamel (University of Thi-Qar Journal of Science, 2009)
The present work is aiming at investigating seasonal variations in levels of some heavymetals (Ni, Cd, and Cu & Zn) in muscles of the crab Sesarma boulengeri. Sampleswere collected from Al-Garaf canal at Thi Qar governorate. The study extended fromMarch 2004 to February 2005. Specimens were collected from a location supply citiesof Basrah, Thi Qar, Shatra and Garaf water's purification boards with crudefreshwater for domestic uses. The surrounding areas are affected with sewage andagricultural disposals. It also represent mixing zone of water masses of variouscompositions. Elements found to vary seasonally in their levels and analyses of musclesindicate that Ni occupied the first position and revealed the highest levels, in general.The minimal recorded accumulative values (200.11 μg/g dry wt) was in Spring and thehighest (243.20 μg/g dry wt) in summer. Zinc occupied second accumulation levels andshowed the minimal (55.13 μg/g dry wt) in spring, whereas Cd, by no means, exhibitedthe minimal concentrations and the lowest value (4.82 μg/g dry wt) was in winter.Causes and effects of trace elements were discussed.